Robust comprehension of natural language instructions by a domestic service robot. (16th December 2016) - Kobori, Takahiro; Nakamura, Tomoaki; Nakano, Mikio; Nagai, Takayuki; Iwahashi, Naoto; Funakoshi, Kotaro; Kaneko, Masahide
Graphical Abstract: Abstract : We present a method through which domestic service robots can comprehend natural language instructions. For each action type, a variety of natural language expressions can be used, for example, the instruction, 'Go to the kitchen' can also be expressed as 'Move to the kitchen.' We are of the view that natural language instructions are intuitive and, therefore, constitute one of the most user-friendly robot instruction methods. In this paper, we propose a method that enables robots to comprehend instructions spoken by a human user in his/her natural language. The proposed method combines action-type classification, which is based on a support vector machine, and slot extraction, which is based on conditional random fields, both of which are required in order for a robot to execute an action. Further, by considering the co-occurrence relationship between the action type and the slots along with the speech recognition score, the proposed method can avoid degradation of the robot's comprehension accuracy in noisy environments, where inaccurate speech recognition can be problematic. We conducted experiments using a Japanese instruction data-set collected using a questionnaire-based survey. Experimental results show that the robot's comprehension accuracy is higher in a noisy environment using our method than when using a baseline method with only a 1-best speech recognition result.